Fostering interdependence to minimise political risks in a European-north African renewable electricity supergrid - Lilliestam, Johan; Ellenbeck, Saskia (Green, 2012)
The option of decarbonisation of the Europeanpower sector with the help of significant imports of renewable electricity from North Africa via a trans-continental electricity Supergrid is increasingly gaining attention. In this paper, we investigate the geopolitical risks to European energy security in such a future, and discuss cornerstones for possible policy strategies to reduce these risks. The strategies are rooted in the interdependence between exporter and importer. We come to the conclusion that fostering and deepening, as opposed to reducing, the dependence of both sides on each other may be a valuable and powerful way to reduce the geopolitical risks of renewable electricity trade between Europe and North Africa. Copyright © 2012 De Gruyter.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Desertec; Energy security; Interdependence; Renewable electricity; Supergrid